2011
DOI: 10.1103/physrevlett.107.020502
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement Irreversibility from Quantum Discord and Quantum Deficit

Abstract: We relate the problem of irreversibility of entanglement with the recently defined measures of quantum correlation--quantum discord and one-way quantum deficit. We show that the entanglement of formation is always strictly larger than the coherent information and the entanglement cost is also larger in most cases. We prove irreversibility of entanglement under local operations and classical communication for a family of entangled states. This family is a generalization of the maximally correlated states for wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(93 citation statements)
references
References 28 publications
(60 reference statements)
1
92
0
Order By: Relevance
“…The same equation is first noted in (Cornelio et al, 2011;Fanchini et al, 2011a) in different contexts (see Secs. V.E and VI.B.3).…”
Section: Entanglement Consumption In State Mergingsupporting
confidence: 62%
“…The same equation is first noted in (Cornelio et al, 2011;Fanchini et al, 2011a) in different contexts (see Secs. V.E and VI.B.3).…”
Section: Entanglement Consumption In State Mergingsupporting
confidence: 62%
“…Over the past decade, quantum discord has received a lot of attentions in Refs. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], and also see the reviews [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it is present in almost all quantum states [14] and the relation between discord and entanglement has been discussed [15][16][17]. In contrast with entanglement, discord can be generated using local noise [18] and it is not monogamous [19].…”
Section: Introductionmentioning
confidence: 99%